A Role for the Krebs Cycle Intermediate Citrate in Metabolic Reprogramming in Innate Immunity and Inflammation - Williams, Niamh C.; O’Neill, Luke A. J. (Frontiers in Immunology, 2018)
Metabolism in immune cells is no longer thought of as merely a process for ATP production, biosynthesis and catabolism. The reprogramming of metabolic pathways upon activation is also for the production of metabolites that can act as immune signalling molecules. Activated dendritic cells (DCs) and macrophages have an altered Krebs cycle, one consequence of which is the accumulation of both citrate and succinate. Citrate is exported from the mitochondria via the mitochondrial citrate carrier. Cytosolic metabolism of citrate to acetyl-coenzyme A (acetyl-CoA) is important for both fatty-acid synthesis and protein acetylation, both of which have been linked to macrophage and DC activation. Citrate-derived itaconate has a direct antibacterial effect and also has been shown to act as an anti-inflammatory agent, inhibiting succinate dehydrogenase. These findings identify citrate as an important metabolite for macrophage and DC effector function.